EFFECT OF KAOLIN ON BIOCHEMICAL PARAMETERS AGAINST AEROMONAS HYDROPHILA IN CYPRINUS CARPIO - Muthana N. Al-Ghazaly,; A. J. Al-Rudainy, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The present study aimed to evaluate the role of kaolin on hematological and biochemical profiles of common carp, Cyprinus carpio infected with Aeromonas hydrophila, A total of 180 of common carp were collected 40 g ; 60 fish were used to determine the median lethal dose LD50 of A. hydrophila, )LD50 was 1.57 × 106 CFU/ml) for 15 days.  120 fish were randomly distributed into six treatment groups (10 fish/treatment in duplicate) as follows:  C- served as control negative group (without infection and treatment); C+ act as control positive group (infected with A. hydrophila but not treatment with Kaolin); T1, T2, T3 and T4 were intraperitoneally (IP) injected with A, hydrophila   (at dose of 0.1 ml) and then treated with Kaolin at concentrations of 2, 4, 6 and 8 g/L respectively.  In hematological indices, the experimental groups of carp (C+, T1, T2, T3 and T4) showed a significant (P